THE EFFECT OF NON-PERFORMING LOANS ON RETURN ON ASSETS AT BANK CIJ BOJONGGAMBIR TASIKMALAYA - Juniar prayoga, Cepi; Mulyani, Fithry Sri; Anggraeni, Windi Ariesti; Hardiyanti, Ade (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
The purpose of this study was to determine the effect of non-performing loans on return on assets. The type of research used is associative / relationship, namely research that aims to determine the relationship between two or more variables. The sample used in this study is the financial statements of non-performing loans of Bank CIJ Bojonggambir Branch in 2016-2020. The statistical method used is simple linear regression analysis. Based on the results of this study, non-performing loans have a significant negative effect on return on assets. This means that the higher the level of non-performing loans, the lower the return on assets.